A new budget for the EU: Negotiations on the multiannual financial framework 2021-2027 - Peter Becker (Stiftung Wissenschaft und Politik (SWP), 2019)
Negotiations on the EU's Multiannual Financial Framework (MFF) are always lengthy, complex and conflictual. This applies to the MFF 2021-2027, which is expected to have a financial volume of around exteuro1.3 trillion. As usual, the negotiations revolve around political priorities, the expenditures determined for each of them, and the distribution of the financial burden among member states. This ongoing process is hampered by the forthcoming Brexit, as the UK has so far contributed substantial amounts to the Union's budget. Furthermore, there are new tasks for the EU which require additional resources, such as the establishment of a defence union, increased protection of the EU's external borders, and the stabilisation of the euro zone. Since the European Commission presented its proposal for a pragmatic reform of the EU budget on 2 May 2018, the member states have been negotiating a comprehensive package. However, cohesion in the coalitions of net contributors and net recipients is dwindling. The delicate negotiation framework makes the course and results of the search for consensus more difficult to foresee, and the actors less predictable. Due to the increasing uncertainty, all participants expect Germany to play a balancing role. Many countries hope that Germany, as the strongest economy and the largest net contributor, will provide additional resources to facilitate a successful conclusion of the negotiations on a new MFF. The German government therefore needs clear and firm ideas about the fields in which it wants to modernise EU policies and to further Europeanise and communitise them.
Keywords: 320